Recent advances in methodologies and applications of cataluminescence sensing. (22nd June 2020) - Hu, Jiaxi; Zhang, Lichun; Su, Yinigying; Lv, Yi
Abstract: Cataluminescence (CTL), a kind of chemiluminescence emitted at the gas–solid interface during catalytic oxidation reactions, has been developed for many decades as a novel and promising gas sensing technique. In this review, we introduce the origin, basic principles, and mechanisms of CTL sensing systems and summarize the recent advances in CTL sensing, focusing on methodologies and extended applications such as in gas selective monitoring, recognition of complex mixture, evaluation for catalytic property and use in high‐performance liquid chromatography, capillary electrophoresis and gas chromatography detectors. In addition, development prospects and some challenges facing CTL‐based sensing are also discussed.